2020
DOI: 10.1001/jamaoto.2019.4328
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of First Injection of Autologous Adipose Tissue–Derived Stromal Vascular Fraction in Human Scarred Vocal Folds

Abstract: IMPORTANCE Patients with scarred vocal folds, whether congenitally or after phonosurgery, often exhibit dysphonia that negatively affects daily life and is difficult to treat. The autologous adipose tissue-derived stromal vascular fraction (ADSVF) is a readily accessible source of cells with angiogenic, anti-inflammatory, immunomodulatory, and regenerative properties. OBJECTIVE To evaluate the feasibility and tolerability of local injections of autologous ADSVF in patients with scarred vocal folds. DESIGN, SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Several in vivo studies on animals reported significant improvements in scarred vocal folds after injection of ASC (immediately after injury or at a longer interval) in both histological and macroscopic aspects of the vocal folds [34] with an excellent tolerance of the procedure. A first clinical trial of SVF injection which enrolled 8 patients was recently reported by our group [35] suggesting a clear improvement in the majority of the vocal parameters obtained at 12 months. However, the etiology of vocal fold scarring is very heterogenous so a better understanding of the mechanisms underlying the efficacy of ASC and SVF is mandatory.…”
Section: Discussionmentioning
confidence: 81%
“…Several in vivo studies on animals reported significant improvements in scarred vocal folds after injection of ASC (immediately after injury or at a longer interval) in both histological and macroscopic aspects of the vocal folds [34] with an excellent tolerance of the procedure. A first clinical trial of SVF injection which enrolled 8 patients was recently reported by our group [35] suggesting a clear improvement in the majority of the vocal parameters obtained at 12 months. However, the etiology of vocal fold scarring is very heterogenous so a better understanding of the mechanisms underlying the efficacy of ASC and SVF is mandatory.…”
Section: Discussionmentioning
confidence: 81%
“…The outcome was improved healing of scarred vocal fold, one year postoperatively [123]. Assistance Publique Hopitaux De Marseille in an open labeled single-group clinical trial enrolling eight 18 years and older patients with vocal fold scarring and dysphonia injected autologous AdSCs and reported the feasibility, safety, and efficacy of the procedure and functional measures of voice handicap index evaluated by laryngostroboscopy [124]. Lo Cicero et al confirmed use of AdSCs in patients who had undergone vocal fold lipoinjection with laryngeal hemiplegia or defects and demonstrated the therapeutic efficacy of this clinical approach and restoration of glottic competence [125].…”
Section: Clinical Trials Of Vocal Fold Scarringmentioning
confidence: 99%
“…Autologous fat tissue research has been conducted to the development of clinical trials with representative results in plastic and reconstruction surgery and regenerative medicine, especially for: breast augmentation [55,56], breast implants preventing complications [57], breast reconstruction deformities correction [56,58], soft tissue augmentation [59,60], supporting fat tissue transplantation [61], facial rejuvenation [62], burns regeneration [63] and fistulas reparation [64]. In addition, some of the clinical trials were orientated in using adipose tissue cells as treatment of various pathologic conditions: degenerative disk disease [65], ischemic disease [66], scarred vocal folds [67] and male stress urinary incontinence [68].…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%